Evaluation of RET Species from Preserved Forests of Konkan Region, Maharashtra State, India - Upadhye, Anuradha S.; Kulkarni, D. K.; Pathak, G. P. (Indian Forester, 2019)
The Western Ghats is bio-rich and particularly Konkan region of Maharashtra possess iconic biodiversity. Today this biodiversity is highly preserved in a special type of vegetation the 'Sacred groves or Devrais or Deorahat'. These vegetation patches are being preserved by local people on religious belief. It is conserved with respect to specific deity on ritual belief or without any deity or offered 'Vatan' to the particular community. These communities are taking care of these virgin forest patches for social, cultural, religious and even for funeral activities. Such forests patches support luxuriant growth of indigenous flora and harbor rare, endangered and threatened (RET) and endemic species. In the present status report, 45 preserved forests from 4 districts of Konkan region were surveyed which results into documentation of 15 RET species and 43 endemic species. These species can be used as future germplasm. The taxon data sheet was prepared for documentation of field observations and analysis was carried out as per guidelines provided by IUCN and CAMP exercise. The collected specimens were deposited at AHMA. Based on this analysis conservation measures can be planned for these 15 RET species and locations can serve as gene banks for respective species.